The path of Biotechnology at the Universidad Nacional Agraria La Molina, Peru - Gutiérrez-Correa, Marcel (2012)
In this paper, I make a historical account of the fifty years that have the degree in biology at the Universidad Nacional Agraria La Molina and gestation, and the beginning, development and maturation of biotechnology in this university. We describe some details of the three most important curricular modifications that led to the establishment of the biotechnology area in the curricula of undergraduate and doctoral programs, as well as their main achievements. The development of biotechnology at the UNALM has influenced the development of this area in Peru not only in the curricular changes that have occurred in several Peruvian universities, but also in the biotechnology research being carried out in many regions of the country. In this historical process, I conclude that the balance is positive and that the best epistemology stream is that which leads through research to find truths usable for solving the problems of Peru and also why not the planet.